Frequency of Relapse Rate after Treatment of Patients Addicted with Drugs Abuse (Opioids) - Ather, Asfiya; Hamdani, Syed Muhammd Akram; Jan, Hina Tariq (Indus Journal of Bioscience Research, 2025)
Objectives: frequency of relapse rate after treatment of patients addicted with drugs abuse (Opioids). Methodology: This descriptive study at CMH Lahore included 60 patients aged 18–60 years with a history of opioid addiction. Data on demographics, addiction history, and relapse, defined as re-use of opioids after detoxification and three months of treatment, were collected using a structured proforma. Patients were followed for three months post-treatment to record relapse occurrences and associated factors. Results: Of 60 patients revealed a relapse rate of 53.3% following opioid detoxification. Relapse was highest among males (56.1%), individuals with primary education (73.3%), and heroin users (58.8%). Age, socioeconomic status, living conditions, and duration of drug use showed no statistically significant associations with relapse. Prior detoxification also did not significantly impact relapse rates. Conclusion: Relapse in opioid addiction is multifactorial, necessitating holistic, individualized approaches to improve outcomes and reduce societal burden, considering demographic and clinical complexities for effective prevention and treatment strategies.